System ochrony zdrowia w Szwajcarii – doświadczenia i rekomendacje dla Polski - Figura, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article pertains to the subject of health policy. The paper examines in detail one of the best health systems in the world, which operates in Switzerland. The aim of the article is a detailed presentation of the functioning of the health system in Switzerland, according to selected criteria. The article was developed based on the study of literature (both national and international positions). The health model adopted and implemented in Switzerland has its advantages and disadvantages. The success of the health system in Switzerland is determined by, among other factors, the operation of many competing companies offering health insurance, broad and at the same time socially acceptable patient co-payment and the development of large-scale private health insurance and high "saturation" of medical personnel within the health system. Concrete proposals to improve the situation in the Polish health care system were indicated, based on the rich experience of the Swiss health system. The solutions adopted in the Swiss health care system should provide inspiration for all decision-makers in Poland.
The health care system in Switzerland – experiences and recommendations for Poland
Keywords: healthcare; Switzerland; health insurance; co-payment